Polycystic ovary syndrome and their implications in metabolic disorders: New targeted therapies for improving reproductive outcomes - Chuffa, Luiz Gustavo De Almeida [UNESP]; Fioruci-Fontanelli, Beatriz Aparecida [UNESP]; Amorim, João Paulo De Arruda (My University, 2013)
The natural process of ovulation occurs when the egg is released from the mature follicle. Although many follicles start growing, only a small number reaches maturity and ovulates. The majority of ovarian follicles suffer a process of apoptosis designated as follicular atresia. The understanding of why only some follicles may ovulate (dominant follicles) is a complex process of which not all facets are known. The ovulation process is not a random event but occurs in response to increased plasma concentrations of luteinizing hormone (LH) and after the ovary has been exposed to this hormone for a certain period of time. Initially, the hypothalamus releases gonadotropin-releasing hormone (GnRH) that sends signals to the pituitary gland to release the hormones LH and follicle stimulating hormone (FSH). The LH and FSH can orchestrate the rate of follicle development and ovarian production of both estrogen and progesterone. Theca cells in the ovary respond to LH stimulation by releasing testosterone, which is converted into estrogen during aromatization by granulosa cells. Additionally, ovarian granulosa-lutein cells are the major sites of progesterone synthesis, which is essential for autocrine regulation of ovulation. Residual cells within ovulated follicles proliferate to form corpora lutea, which remains producing steroid hormones during pregnancy. Dysfunctions of hypothalamus-pituitary-ovary axis alter the ovulation process, leading to consecutive anovulation and subsequent infertility. Anovulation and tubal diseases are the main causes of infertility in women. The anovulation occurs in response to various hormonal disorders. Notably, a common endocrinopathy related to anovulation and infertility is the so called polycystic ovary syndrome (PCOS). The PCOS affects approximately 5% to 10% of women in the reproductive age and is characterized by at least 2 of the following 3 criteria described below: (1) oligo-ovulation or anovulation, (2) clinical or biochemical evidence of hyperandrogenism, and (3) polycystic ovaries on ultrasound assessment (more than 12 small antral follicles). Finally, the reduced fertility in women with PCOS may be attributed not only to anovulation consequences but also to both effects of hyperandrogenism and endometrial impairments. This chapter will present several points of PCOS, and some potential therapeutic targets focusing in standard and alternative treatment methodologies, in order to improve reproductive outcome of women with PCOS. © 2013 by Nova Science Publishers, Inc. All rights reserved.